Enlarged Pericarotid Lymph Nodes Suggest Recent Ischemic Symptoms in Patients with Carotid Atherosclerosis - Sun, Tao; Wang, Fei; He, Yiming; Mao, Bo; Han, Mengtao; Liu, Han; Zhao, Peng; Li, Xingang; Wang, Donghai (Frontiers in Immunology, 2022)
Atherosclerosis is a chronic inflammatory disease closely associated with immunological activity. Lymph nodes (LNs) are essential secondary lymphoid organs, in which complex immune responses occur. Enlarged LNs are commonly observed around inflamed tissues or tumors; however, their role in atherosclerosis is not well understood. We hypothesized that enlarged pericarotid LNs would be present in symptomatic patients with carotid atherosclerosis. Therefore, we recorded the size of LNs around the carotid artery during surgery in patients undergoing carotid endarterectomy (CEA) for carotid atherosclerotic stenosis. Patients were stratified by enlarged LNs, defined as a diameter ≥ 10mm in the transverse diameters. Demographic and clinical data of participants were measured and analyzed. Hematoxylin and eosin (H&E), Sirius red, DAB-enhanced Perls’ Prussian blue, alizarin red, and immunohistochemistry (IHC) staining were performed for composition identification of plaques or LNs. Symptomatic patients were defined as those presenting with an ipsilateral cerebral ischemic event. Compared with patients with non-enlarged LNs, patients with enlarged LNs were more likely to be symptomatic (22/32, 68.8% versus 9/40, 22.5%, P < 0.001) and use calcium channel blocker drugs (17/32, 53.1% versus 10/40, 25%, P=0.014). In addition, they showed lower body mass index (mean ± SD: 24.00 ± 2.66 versus 25.34 ± 2.56 kg/m2, P=0.034), lower weight (median [interquartile range]: 64 [60.00-76.00] versus 72.5 [65.00-77.50] Kg, P = 0.046) and higher diastolic blood pressure (mean ± SD: 78.94 ± 9.30 versus 73.93 ± 8.84 mmHg, P = 0.022). The plague from patients with enlarged LNs exhibited a lower relative percentage of fibrous tissue (29.49 ± 10.73% versus 34.62 ± 10.33%, P = 0.041). The enlarged LNs remained oval-shaped by visual inspection. Compared to non-enlarged LNs, the predominant changes in enlarged LNs were atrophic lymphatic sinuses and dilated LNs parenchyma. Enlarged LNs contained more germinal centers and lymphocytes. In conclusion, symptomatic patients with carotid atherosclerosis have enlarged pericarotid LNs. The current study supports the conclusion that enlarged LNs with an activated and enhanced adaptive immune response may indicate plaque instability. Pericarotid LNs will be a promising marker of plaque stability and may be a potential therapeutic target in patients with carotid atherosclerosis.